Minimizing the time for UAV to reach a moving target (MCIT: Proceedings of International scientific and practical conference, 2023)
In this study, we address the control challenges of directing a flying object, specifically a drone, to a designated target, utilizing coordinates relayed from a monitoring device. Monitoring device delivers information about coordinates of suspicious object to drone.  Upon receiving signals from a monitoring device about potential threats on the ground, the drone is tasked to promptly respond, identify, and neutralize the suspicious object. This article deals with the issue of controlling the process of flying snow to the target in the shortest possible time.